Positive solutions of second-order singular boundary value problem with a Laplace-like operator - Ge Weigao; Ren Jingli (Journal of Inequalities and Applications, 2005)
By use of the concavity of solution for an associate boundary value problem, existence criteria of positive solutions are given for the Dirichlet BVP , , , where is odd and continuous with , , and may change sign and be singular along a curve in .